Determination of Reserpine and Yohimbine in Rauvolfia by High-Performance Liquid Chromatography - Ma, Sha; Xue, Jingjiao; Cao, Jingli; He, Shunqin; Hu, Qiufen; Yang, Guangyu (Asian Journal of Chemistry, 2010)
A new direct high performance liquid chromatography (HPLC) analytical method for the determination of reserpine and yohimbine in Rauvolfia has been developed. The reserpine and yohimbine was separated on a Zorbax stable bound (2.1 mm × 50 mm, 1.8 mm) C18 column with 50 % acetonitrile (containing 0.01 mol L-1 1,2-ethylenediamine) as the mobile phase and detected with UV detector at 280 nm. This method provides good reproducibility and sensitivity for the quantification of reserpine and yohimbine. The relative standard derivation of overall intra-day variations were less than 2 % and the relative standard derivation of inter-day variations were less than 2.5 %. The standard recoveries (three different concentrations of markers: 0.1, 0.5 and 2.0 mg) were ranged from 97-102 %.